2018
DOI: 10.1111/syen.12277
|View full text |Cite
|
Sign up to set email alerts
|

Diversification patterns of the grasshopper genus Zoniopoda Stål (Romaleidae, Acridoidea, Orthoptera) in open vegetation biomes of South America

Abstract: The open vegetation biomes, within the limits of the Chacoan subregion, occur along a diagonal in eastern South America covering a large range of environmental conditions. In order to contribute to the knowledge on the biodiversity of these open biomes, we analysed the phylogenetic relationships of the grasshopper genus Zoniopoda to the remaining South American Romaleinae, and examined the biogeographical patterns of diversification of the genus. The study is based on morphological and molecular (COI and H3) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Extraction and amplification of two mitochondrial gene fragments [NADH dehydrogenase subunit 2 (ND2) and cytochrome c oxidase subunit I (COI)] and one nuclear gene fragment [histone 3 (H3)] were performed using the methods of Husemann et al (2013). Previous studies have demonstrated that these markers are useful for comparisons among grasshopper species (Husemann et al, 2013;Guzman et al, 2017;Pocco et al, 2018;Scattolini et al, 2018). Sequences for the three gene regions were examined, trimmed and aligned using Geneious 6.1.6 (http:// www.geneious.com; Kearse et al, 2012)).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Extraction and amplification of two mitochondrial gene fragments [NADH dehydrogenase subunit 2 (ND2) and cytochrome c oxidase subunit I (COI)] and one nuclear gene fragment [histone 3 (H3)] were performed using the methods of Husemann et al (2013). Previous studies have demonstrated that these markers are useful for comparisons among grasshopper species (Husemann et al, 2013;Guzman et al, 2017;Pocco et al, 2018;Scattolini et al, 2018). Sequences for the three gene regions were examined, trimmed and aligned using Geneious 6.1.6 (http:// www.geneious.com; Kearse et al, 2012)).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The length of the hind femur was measured from the dorso-proximal lobe to the distal extremity. High-resolution photographs were captured and processed as described in Pocco et al (2018). The group classification follows Cigliano et al (2021).…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…Pilgrim & Vondohlen (2008) studied the phylogenetic relationships of Sympetrinae based on molecular data (mitochondrial loci 16S and 12S rRNA) and morphological traits (38 wing venation characters); even though the study did not involve direct comparison of phylogenetic trees based on the two types of information, its conclusion was that the characteristics of the wing veins might be useless in the analysis of relationships due to homoplasy. However, morphological and genetic structure may undergo synchronous evolution in other insects, such as the pronotum and genital segments of grasshopper genus Zoniopoda (Pocco et al, 2018), and the wing veins and genital segments of Euptychiina butterflies (Marín et al, 2017), indicating that phylogenetic information may be contained in morphological features of some insects.…”
Section: Evaluation Of Genetic Information On Wing Shapementioning
confidence: 99%